The Effectiveness of Various Aromatic Vegetable Extracts to Control Fruit Fly (Bactrocera dorsalis) Pests in Chili - Juniaty Arruan Bulawan; La Mpia; Djunarlin Tojang; H. Hasbiadi; R. Rahim (Universitas Sembilanbelas November Kolaka, 2022)
Chili is one of the most valuable horticultural commodities, yet production is declining year after year. Fruit fly pests, which cause losses of 30-60%, are a stumbling block to growing chili production. Several types of aromatic vegetable extracts were used in this investigation, including clove leaves, babadotan, citronella leaves, and basil leaves, all of which have been found to contain methyl eugenol components. The goals of this study were to find the most efficient form of aromatic vegetable extract for usage as a fruit fly pest attractant and to see how different aromatic vegetable extracts affected the intensity of fruit fly pests. The treatments were set up in a completely random order and were repeated three times. Planting chilies, creating aromatic vegetable extracts, making traps, deploying traps in the field, estimating the number of trapped fruit fly populations, and finally assessing the results were all part of this study. P1 = clove leaf extract, P2 = babadotan leaf extract, P3 = citronella leaf extract, and P4 = basil leaf extract are the therapies that will be provided. Bactrocera dorsalis was identified as the captured fruit fly species. The clove leaf extract treatment had the most fruit flies captured (35.67), while the babadotan leaf extract had the least (29.76), but none of the treatments were substantially different